Obesity suppresses tumor attributable PSA, affecting risk categorization. Issue 5 (May 2018) - Chow, Ken; Mangiola, Stefano; Vazirani, Jaideep; Peters, Justin S; Costello, Anthony J; Hovens, Christopher M; Corcoran, Niall M
Abstract : Obesity is linked with more aggressive prostate cancer and higher rates of disease recurrence post treatment. It is unclear if this is due to specific tumor-promoting effects of obesity or diagnostic bias. Patients undergoing prostatectomy were categorized according to their body mass index (BMI). Expected prostate-specific antigen (PSA) levels were calculated for each patient based on tumor characteristics. The effect of obesity on the accuracy of pre-treatment risk categorization was determined, and mediation analysis was used to identify the contribution of biologic vs non-biologic mechanisms to the observed increased risk of biochemical recurrence. Residual tumor-promoting effects were estimated in a survival model controlling for diagnostic error. The following results were obtained. The analysis included 1587 patients. Despite similar rates of adverse pathological features at prostatectomy, biochemical recurrence rates were significantly higher in very obese patients, which persisted after adjustment for stage, grade and PSA. Tumor volume however correlated significantly with BMI ( P  = 0.004), and the difference in predicted and observed 'tumor-attributable' PSA (Delta-PSA) in very obese patients was greater than three times higher than that of healthy patients ( P  = 0.0067). Regression analysis indicated that the effect of BMI on tumor volume was fully mediated indirectly by its effect on PSA. Inclusion of this diagnostic error as a covariate in the survival analysis attenuated the effect of BMI on recurrence. In conclusion, being very obese suppresses tumor-associated PSA resulting in a diagnostic bias that is responsible for errors in risk classification, and potentially contributes to a delay in initial presentation.